Residential heating and ventilation - McCabe, John. (Lawrenceville, NJ : Shopware, 2008)
This program illustrates several different types of heating systems, including forced-air gas furnaces, high-efficiency furnaces, and hot air systems. Differenct types of ignition and fuels are covered, along with the major elements of gas furnaces, including solenoids, burners, manifolds, heat exchangers, and more. Air flow components such as supply and return plenums, air filters, and split capacitor motors are also explained, in addition to thermostats, pilot safety switches, and gas valves. Viewers will get a look at the automated service centers at the heart of many modern large office buildings, which maintain climate control using high-tech sensors and adjustment systems.
Technical advisor, Phil Mest.
Host: Alan Pratt.
Keywords: Dwellings -- Heating and ventilation; Furnaces; Heating